Cellulose nanocrystals and related nanocomposites: Review of some properties and challenges - Mariano, Marcos; El Kissi, Nadia; Dufresne, Alain (Journal of polymer science. Part B, Polymer physics, 2014)
ABSTRACT Cellulosic nanoparticles with high Young's modulus, crystallinity, specific surface area, and aspect ratio can be found in the natural structure of plant fibers. Indeed, lignocellulosic fibers consist of semicrystalline cellulose nanofibrils embedded in an amorphous matrix mainly composed of lignin and hemicelluloses. These nanostructures give the mechanical strength to higher plant cells, and are biodegradable, renewable, resistant, and widely available to produce nanocomposites with low density, and improved and controlled mechanical, optical, and barrier properties. Nanoparticles can be extracted from cellulose using a top‐down mechanically or chemically assisted deconstructing strategy, and owing to their highly reactive surface ensuing nanomaterials can be chemically modified to tailor their properties for a wide range of applications. This review is limited to cellulose chemically extracted nanocrystals and aims to provide an overview about several aspects that involve this material, including sources, properties, challenges, and perspectives. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 791–806 Impressive mechanical properties and reinforcing capability, abundance, low weight, renewability, and biodegradability make cellulose nanocrystals ideal candidates for use in polymer nanocomposites. This Review also looks at the broad range of potential applications of these nanoparticles, as well as the remaining questions in the field.